RadShield: semiautomated shielding design using a floor plan driven graphical user interface. (8th September 2016) - DeLorenzo, Matthew C.; Wu, Dee H.; Yang, Kai; Rutel, Isaac B.
Abstract : The purpose of this study was to introduce and describe the development of RadShield, a Java‐based graphical user interface (GUI), which provides a base design that uniquely performs thorough, spatially distributed calculations at many points and reports the maximum air‐kerma rate and barrier thickness for each barrier pursuant to NCRP Report 147 methodology. Semiautomated shielding design calculations are validated by two approaches: a geometry‐based approach and a manual approach. A series of geometry‐based equations were derived giving the maximum air‐kerma rate magnitude and location through a first derivative root finding approach. The second approach consisted of comparing RadShield results with those found by manual shielding design by an American Board of Radiology (ABR)‐certified medical physicist for two clinical room situations: two adjacent catheterization labs, and a radiographic and fluoroscopic (R&F) exam room. RadShield's efficacy in finding the maximum air‐kerma rate was compared against the geometry‐based approach and the overall shielding recommendations by RadShield were compared against the medical physicist's shielding results. Percentage errors between the geometry‐based approach and RadShield's approach in finding the magnitude and location of the maximum air‐kerma rate was within 0.00124% and 14 mm. RadShield's barrier thickness calculations were found to be within 0.156 mm lead (Pb) and 0.150 mm lead (Pb) for the adjacent catheterization labs and R&F room examples, respectively. However, within the R&F room example, differences in locating the most sensitive calculation point on the floor plan for one of the barriers was not considered in the medical physicist's calculation and was revealed by the RadShield calculations. RadShield is shown to accurately find the maximum values of air‐kerma rate and barrier thickness using NCRP Report 147 methodology. Visual inspection alone of the 2D X‐ray exam distribution by a medical physicist may not be sufficient to accurately select the point of maximum air‐kerma rate or barrier thickness. PACS number(s): 87.55.N, 87.52.‐g, 87.59.Bh, 87.57.‐s